UNDERSTANDING STUDENTS’ LEARNING EXPERIENCES IN THE DIGITAL AGE - Muhammad Shabir; Amalul Umam (STKIP Siliwangi, 2020)
The growth of digital technology has significantly shaped the way students learn. Surrounded by web-enhanced learning sources, various learning activities are available that have contributed to the change in students’ learning. Based on an interpretative approach of the Complexity Theory, the current qualitative case study aims to investigate how students learn English in the digital era. The sample consists of 42 students of a university in Bogor, West Java, Indonesia. The instrument used for collecting the data includes (a) questionnaire used to examine the accessibility to the digital based learning of the students selected for the sample and (b) narrative frames to explore the students’ learning experiences in the digital era. The study reveals that students’ learning in the digital age is self-organizing which offers the tendency for the students to be autonomous. The study also affirms that the current in-class teaching and learning practices do not align with students’ learning experiences in the digital age. The students felt what they got in classes has failed to satisfy and enrich their understanding of the subject taught. It is thus, as an implication the study has, the integration of learning sources into digital learning sources is encouraged. Keywords: Digital age, Learning experiences, Complexity theory